Semi-Structured Interview for Personality Functioning (STiP-5.1): Psychometric Properties of the Lithuanian Version in a Sample of Adolescents - Barkauskienė, Rasa; Gaudiešiūtė, Elena; Saročkaitė, Agnė; Binkauskas, Ugnius; Gerliakaitė, Ieva; Pliučienė, Kristina (Psichologija, 2024)
In recent years the dimensional approach in personality pathology has gained prominence and the level of personality functioning (LPF) has emerged as the primary criterion of personality disorder. LPF is defined as functioning of self- and interpersonal processes encompassing the continuum from adaptive to impaired. Recognizing that the early intervention is crucial for personality disorder, reliable and valid diagnostic methods are necessary for identifying the risk of personality pathology during adolescence. The Semi-Structured Interview for Personality Functioning (STiP-5.1) has shown good psychometric properties among adults, yet has been little researched in adolescents. The aim of this study is to evaluate the psychometric properties of the Lithuanian version of STiP-5.1 in a sample comprising adolescents receiving mental health services and typical (normative) development. The study involved 178 adolescents (aged 11–18; clinical (n = 104) and normative (n = 74) groups). Besides the Semi-Structured Interview for Personality Functioning (STiP-5.1), other measures to assess self-reported level of personality functioning, borderline personality features, and maladaptive personality traits along with measures of psychopathological symptoms, including internalizing and externalizing difficulties, were used. The findings suggest a unidimensional structure of STiP-5.1. High internal consistency and good inter-rater reliability for the overall STiP-5.1 scale were found along with results indicating strong associations between STiP-5.1 and other personality pathology measures in support for construct validity. The instrument differentiated between the normative development and clinical samples with large effect size. In conclusion, the results reveal adequate psychometric characteristics of the Lithuanian version of STiP-5.1 supporting its potential application with adolescents experiencing mental health difficulties.